(untitled) (International Journal of Environmental Sciences, 2025)
Background: Sinus tarsi syndrome (STS) is an uncommon cause of chronic lateral ankle pain and instability, often developing after ankle sprains due to subtalar joint ligament injuries. The resulting subtalar instability leads to synovitis and fibrotic tissue infiltration in the sinus tarsi space. Optimal management is not well established, but conservative therapy is generally first-line. Case Presentation: A 27-year-old male recreational athlete presented with persistent right anterolateral ankle pain for 7 months following a severe inversion injury. He reported deep ankle pain (VAS 7/10) aggravated by weight-bearing and uneven ground, with a sensation of hindfoot instability and “giving way.” Physical exam showed tenderness over the sinus tarsi (lateral opening of the subtalar joint) and pain at end-range inversion and plantarflexion. Notably, he had bilateral pes planus (flat arches), which can increase subtalar stress. The talar tilt (inversion stress) test was positive, suggesting lateral ankle ligament laxity. Investigations: Blood tests (including rheumatoid factor and uric acid) were normal, reducing suspicion of inflammatory arthritis or gout. Ankle radiographs were unremarkable. Magnetic resonance imaging (MRI) of the ankle revealed fluid and oedema in the sinus tarsi with T2 hyperintense signal replacing the normal fat, and injuries to the interosseous talocalcaneal and cervical ligaments – findings characteristic of sinus tarsi syndrome. These imaging results confirmed the clinical diagnosis. A diagnostic sinus tarsi injection was considered but not performed (the patient declined this procedure), so we proceeded directly with conservative management. Intervention: The patient underwent a 6-week conservative rehabilitation program. Initial measures included rest from aggravating activities, oral nonsteroidal anti-inflammatory drugs (NSAIDs) for pain relief, and footwear modification (arch-support insoles to correct pes planus). A structured physiotherapy regimen was implemented focusing on proprioceptive and balance training, ankle strengthening exercises, and range-of-motion maintenance. Balance exercises (e.g. single-leg stands on unstable surfaces, wobble board training) were emphasized to improve subtalar joint proprioception and postural control. Theraband resistive exercises targeting the peroneal and tibialis muscles were used to enhance dynamic support of the subtalar joint. Kinesiology taping was applied around the ankle (including a subtalar sling taping technique) to provide external support and feedback during activities. These interventions align with recommended conservative treatments for STS, which include balance/proprioceptive training, muscle strengthening, bracing or taping, and foot orthoses. The goal was to restore neuromuscular control and compensate for the loss of ligamentous stability. Outcomes: By the end of the rehabilitation program, the patient’s symptoms had improved substantially. Ankle pain decreased to VAS 1–2/10 with only occasional mild twinges on uneven ground. Instability feelings resolved; he could jog and cut laterally without the previous “giving way.” On examination, sinus tarsi tenderness markedly diminished and the subtalar range was pain free. He returned to recreational sports (cricket) at 3 months post-injury with an ankle brace for additional support. At 6-month follow-up, he remained asymptomatic in daily activities and sports, with no recurrence of instability. This functional recovery without invasive intervention highlights the effectiveness of the conservative, proprioception-focused management. Conclusion: This case demonstrates that sinus tarsi syndrome in an athlete can be successfully managed with non-operative treatment centred on proprioceptive and strengthening rehabilitation. Restoration of subtalar stability through targeted neuromuscular training addressed the underlying ligamentous injury and instability, leading to resolution of chronic pain. Proprioceptive rehabilitation may be a critical component in conservative management of STS, potentially obviating the need for injections or surgery in similar cases. Sports medicine clinicians should maintain a high index of suspicion for STS in patients with chronic ankle pain post-sprain and consider comprehensive rehabilitation to target subtalar joint instability.